KESESUAIAN PENERAPAN EUTHANASIA TERHADAP PASIEN KONDISI TERMINAL ATAS PERSETUJUAN KELUARGA DALAM HUKUM POSITIF INDONESIA - Fachrezi, Mochammad Alwi; Michael, Tomy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2024)
Normatively, the act of euthanasia in Indonesia is prohibited because in the Criminal Code it’s classified as a criminal offence as it means deprivation of the patient's life. The Indonesian medical code of ethics confirms the same thing that doctors are not allowed to perform euthanasia because it’s very contrary to their morality, which should protect the patient's life. However, Permenkes No. 37/2014 confirms that doctors can actually perform euthanasia on patients with certain procedures. The purpose of this study is to determine the suitability of the application of euthanasia to terminal condition patients with family consent in Indonesian positive law. The type of research used is normative legal research using a statute approach; conceptual approach; and comparative approach. The results obtained in this study are that the act of euthanasia cannot be classified as a criminal offence if the doctor does it for patients with certain conditions and according to procedures. Thus, if reviewed in positive law, the application of euthanasia in terminal patients with family consent is considered appropriate. Belgium and Luxembourg have legitimised euthanasia in their respective laws and regulations. Indonesia should be able to follow in the footsteps of Belgium and Luxembourg in legitimising euthanasia. The contradiction between the Indonesian Criminal Code and Code of Medical Ethics with Permenkes No. 37/2014 should be harmonised by updating the legislation that more specifically and firmly regulates euthanasia by including the determination of the patient's condition and certain possible procedures in applying for euthanasia, and providing criminal sanctions for doctors who perform euthanasia not in accordance with procedures. This aims to provide legal certainty for doctors and the patient's family when performing euthanasia, and minimise misinterpretation of euthanasia as in the Indonesian Criminal Code.